1993
DOI: 10.1084/jem.177.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated potassium channels regulate calcium-dependent pathways involved in human T lymphocyte activation.

Abstract: SummaryThe role that potassium channels play in human T lymphocyte activation has been investigated by using specific potassium channel probes. Charybdotoxin (ChTX), a blocker of small conductance Ca 2 +-activated potassium channels (Pc,c,) and voltage-gated potassium channels (PK,v) that are present in human T cells, inhibits the activation of these cells. ChTX blocks T cell activation induced by signals (e.g., anti-CD2, anti-CD3, ionomycin) that elicit a rise in intracellular calcium ([Ca2+]i) by preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(131 citation statements)
references
References 31 publications
2
128
1
Order By: Relevance
“…More emerging evidence suggest that K + channels play a crucial role in proliferation control in different cell types including corneal epithelial cells (Decoursey et al, 1987;Freedman et al, 1992;Day et al, 1993;Deutsch and Chen, 1993;Pappone and Ortiz-Miranda, 1993;Xu et al, 1996Xu et al, ,1999Wang et al, 1997;Roderick et al, 2003). The activation of K + channels is involved in the onset of cellular events associated with both T-and B-lymphocyte activation (Amigorena et al, 1990a,b;Lin et al, 1993). Enhanced K + channel expression or K + channel activity is associated with mitogenesis in several cell types (DeCoursey et al, 1984;Price et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More emerging evidence suggest that K + channels play a crucial role in proliferation control in different cell types including corneal epithelial cells (Decoursey et al, 1987;Freedman et al, 1992;Day et al, 1993;Deutsch and Chen, 1993;Pappone and Ortiz-Miranda, 1993;Xu et al, 1996Xu et al, ,1999Wang et al, 1997;Roderick et al, 2003). The activation of K + channels is involved in the onset of cellular events associated with both T-and B-lymphocyte activation (Amigorena et al, 1990a,b;Lin et al, 1993). Enhanced K + channel expression or K + channel activity is associated with mitogenesis in several cell types (DeCoursey et al, 1984;Price et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced K + channel expression or K + channel activity is associated with mitogenesis in several cell types (DeCoursey et al, 1984;Price et al, 1989). Suppression of K + channel activity by blockers in culture significantly inhibits cell proliferation (Deterre et al, 1981;Amigorena et al, 1990b;Dubois and Rouzaire-Dubois, 1993;Lin et al, 1993). K + channel activity has been found to be a key determinant for cell progression through the G 1 checkpoint of the cell cycle (Lewis and Cahalan, 1990;Dubois and Rouzaire-Dubois, 1993;Xu et al, 1996;Roderick et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In T cells, this crucial influx of Ca 2+ is only possible if they can keep their membrane potential negative by a counterbalance of K + efflux through K v 1.3 and/or K Ca 3.1 (38,57), and both channels are regarded as targets for immunosuppression (38). In the current study, we demonstrated that e-LXA 4 inhibits K v 1.3 in LPS-stimulated cells.…”
Section: Early Effects Of E-lxa 4 On K V and K Irmentioning
confidence: 99%
“…ϩ channels in T lymphocytes, the voltage-gated Kv1.3 channel (also known as KCNA3 (HUGO nomenclature)) and the Ca 2ϩ -activated IKCa1 channel (also known as KCNN4 (HUGO nomenclature); K Ca 3.1 (International Union of Pharmacology nomenclature) (1)), regulate Ca 2ϩ signaling by controlling the membrane potential of lymphocytes (2)(3)(4)(5)(6)(7). During activation, inositol 1,4,5-triphosphate generation induces the release of Ca 2ϩ from internal stores.…”
Section: T Wo Kmentioning
confidence: 99%